Diagnosis, treatment, and prevention of 2019 novel coronavirus infection in children: experts’ consensus statement - Shen, Kunling; Yang, Yonghong; Wang, Tianyou; Zhao, Dongchi; Jiang, Yi; Jin, Runming; Zheng, Yuejie; Xu, Baoping; Xie, Zhengde; Lin, Likai; Shang, Yunxiao; Lu, Xiaoxia; et al. (World journal of pediatrics : WJP, 2020)
Since the outbreak of 2019 novel coronavirus infection (2019-nCoV) in Wuhan City, China, by January 30, 2020, a total of 9692 confirmed cases and 15,238 suspected cases have been reported around 31 provinces or cities in China. Among the confirmed cases, 1527 were severe cases, 171 had recovered and been discharged at home, and 213 died. And among these cases, a total of 28 children aged from 1 month to 17 years have been reported in China. For standardizing prevention and management of 2019-nCoV infections in children, we called up an experts’ committee to formulate this experts’ consensus statement. This statement is based on the Novel Coronavirus Infection Pneumonia Diagnosis and Treatment Standards (the fourth edition) (National Health Committee) and other previous diagnosis and treatment strategies for pediatric virus infections. The present consensus statement summarizes current strategies on diagnosis, treatment, and prevention of 2019-nCoV infection in children.